Soil Organic Matter, Soil Structure, and Bacterial Community Structure in a Post-Agricultural Landscape - Yavitt, Joseph B.; Pipes, Gwendolyn T.; Olmos, Emily C.; Zhang, Jiangbo; Shapleigh, James P. (Frontiers in Earth Science, 2021)
Converting forest and wetland landscapes to agriculture has shown to result in a loss of organic matter, structure, and microbial diversity in the converted soil but recovery of post-agricultural soils remains poorly understood. Here we coupled landscape-scale surveys of soil 1) carbon and nitrogen levels, 2) aggregation, and 3) bacterial metagenomes to investigate soil recovery after 30 years in sites with soils ranging from well drained to poorly drained. Sites with no evidence of past agriculture (Reference) served as recovery endpoints. A secondary aim evaluated the role of nitrogen-fixing symbiosis, here associated with alder (Alnus incana) trees, in soil restoration. Soil carbon levels in restored sites (3.5%) were comparable to levels in a present-day farm (3.4%) but much lower than in Reference sites (>7.3%). The same trend occurred with soil nitrogen levels. Sites with alder trees had more acidic soil pH values. Alder trees promoted soil structure with macroaggregates being the largest fraction of bulk soil (75%). Natural abundance of stable nitrogen isotopes suggested extensive decay of organic matter within aggregates. Comparison of total reads from the soil metagenomes indicated the bacterial community in restored sites were more comparable to the present-day farm than Reference sites, except for a well-drained soil with alder. Dissimilarity among sites in terms of gene abundances in soil bacterial community occurred in carbon metabolism, membrane transport, and genetic repair pathways. Soil recovery in post-agricultural landscapes is slow when agriculture caused a large loss of soil organic matter, as is the case in our study, and when the soil bacterial community structure changed markedly, as it did in our study. However, fairly rapid recovery of soil structure, as we noted in our study, is promising, and now we need a better understanding of plant species that improve soil structure for restoration of both well-drained and poorly drained soils.